Efektivitas Metode Tahfidzul Qur'an terhadap Retensi Hafalan Santri di Pondok Pesantren Pandanaran Indonesia dan Ma'had Aman Bistari Malaysia - Khoirunisa, Himawati; Khusniyati Sururiyah, Siti; Amirah Binti Mohd Fuad, Hidayatul (Kartika: Jurnal Studi Keislaman, 2025)
Academic concerns remain regarding the differing levels of memorization retention produced by various Qur’anic memorization methods, particularly between traditional sanad-based systems and modern technology-assisted approaches. These variations raise questions about which pedagogical model is most effective in strengthening long-term retention. This study aims to analyze and compare the effectiveness of tahfidzul Qur’an learning methods at Pondok Pesantren Sunan Pandanaran, Indonesia, and Ma’had Tahfiz Vokasi Aman Bistari, Malaysia, with a specific focus on students’ memorization retention. Using a comparative qualitative approach, data were collected through participant observation, in-depth interviews, and documentation study in both institutions. The results indicate that Pondok Pesantren Pandanaran excels in maintaining long-term retention through talaqqi, murāja‘ah, and takrār, supported by sanad-based discipline and a strong spiritual environment. In contrast, Ma’had Aman Bistari demonstrates higher efficiency and flexibility through digital mentoring and the use of tahfidz applications. These findings imply the need for an integrated model that combines traditional spiritual-based methods with modern technological tools to develop an adaptive and sustainable approach to Qur’anic memorization in the digital era.